The Ultrasonic-Assisted Synthesis of Copper Borates by Using Different Boron Sources - Dumanli, Fatma Tugce Senberber; Karaagac, Sibel Kavci; Kipcak, Azmi Seyhun; Derun, Emek Moroydor (PLEIADES PUBLISHING LTD, 2024)
The effect of ultrasound energy on hydrothermal synthesis of metal borates and on the characteristic features of synthesized copper borates was investigated. In ultrasonic-assisted hydrothermal synthesis, the reaction parameters such as boron source, reaction temperature and time were optimized. The synthesis was achieved in the modest conditions of 60 degrees C-2.5 min and 70 degrees C-15 min for the boron sources borax and tincalconite, respectively. The obtained phases were identified as the compound of copper borate (Cu(BO2)2) with the powder diffraction file no. 00-001-0472. The reaction yields were also increased from 48 to 75% with modification of experimental procedure. The observed characteristic stretchings in spectral analyses proved the functional groups of three and four coordinated boron to oxygen bands. In the morphological analyses, less agglomerates were observed at the samples produced by using the boron source of borax than tincalconite. The results exhibited the beneficial effects of probable usage of the ultrasound energy on both the practical synthesis and the increase of characteristics.
Keywords: cooper; borate; X-ray methods; morphology; spectroscopy; CUBIC SUPRAMOLECULAR CAGES; OPTICAL-PROPERTIES; CUBO2; Materials Science